1973
DOI: 10.1093/clinchem/19.12.1380
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Intra-Individual Variation of Serum Constituents: 2. Effects of Exercise and Diet on Variation of Serum Constituents in Healthy Subjects

Abstract: A previous report of within-day variation of serum constituents was based on values in healthy subjects who did not undergo strenuous exercise and who were in a fasting state. In this study we consider the effects of exercise and of a noon meal on the same serum constituents. The statistical significance (t-test) was computed on the basis of the ratios of values (after/before) on the day of exercise vs. the ratios on the nonexercise day, or, for the effect of meal, the ratios of values (after/before the noon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…Bilirubin, γGT and ALP were almost unaltered during the 7‐day measurement period. This finding was expected, as these enzymes are not present in muscle tissue, and is also in accordance with a previous study [18].…”
Section: Discussionsupporting
confidence: 94%
“…Bilirubin, γGT and ALP were almost unaltered during the 7‐day measurement period. This finding was expected, as these enzymes are not present in muscle tissue, and is also in accordance with a previous study [18].…”
Section: Discussionsupporting
confidence: 94%
“…The 96-hour fast incorporated into this study protocol achieved the desired outcome with loss of the 24-hour rhythm of serum phosphate from a group of normal adult male subjects. The rcsult, together with the accompanying reduction in the mean 24-hour serum adjusted calcium concentration, is consistent with the findings of other fasting studies (Statland et al, 1973;Elia et al, 1984). Of major significance, however, is that unlike the one previous study in which it was examined (Jubiz et al, 1972) we have demonstrated that our fasting protocol has led to attenuation of the normal circadian rhythm of PTH(1-84) as measured both by direct immunoreactivity and indirect bioactivity (NcAMP).…”
Section: Discussioncontrasting
confidence: 55%
“…We have tried to address this difficulty by using thresholds defined by percentiles of our data. Glucose levels are likely to fluctuate more in non-fasting samples than cholesterol levels, 53 and we therefore selected a relatively high cut-off for glucose in order to have reasonable specificity and sensitivity. Given that our estimated prevalence of MHO is within the range seen in previous studies, we feel that this is unlikely to have strongly biased our results, which remained similar if lower cut-points were used for cholesterol and glucose.…”
Section: Discussionmentioning
confidence: 99%